Assessing the effectiveness of two intervention methods for stony coral tissue loss disease on Montastraea cavernosa - Erin N. Shilling (Nature Portfolio, 2021)
Abstract Stony coral tissue loss disease (SCTLD) was first observed in Florida in 2014 and has since spread to multiple coral reefs across the wider Caribbean. The northern section of Florida’s Coral Reef has been heavily impacted by this outbreak, with some reefs experiencing as much as a 60% loss of living coral tissue area. We experimentally assessed the effectiveness of two intervention treatments on SCTLD-affected Montastraea cavernosa colonies in situ. Colonies were tagged and divided into three treatment groups: (1) chlorinated epoxy, (2) amoxicillin combined with CoreRx/Ocean Alchemists Base 2B, and (3) untreated controls. The experimental colonies were monitored periodically over 11 months to assess treatment effectiveness by tracking lesion development and overall disease status. The Base 2B plus amoxicillin treatment had a 95% success rate at healing individual disease lesions but did not necessarily prevent treated colonies from developing new lesions over time. Chlorinated epoxy treatments were not significantly different from untreated control colonies, suggesting that chlorinated epoxy treatments are an ineffective intervention technique for SCTLD. The results of this experiment expand management options during coral disease outbreaks and contribute to overall knowledge regarding coral health and disease.